Cross-cultural adaptation and validation of the family needs assessment scale for Brazilian families of children and adolescents with disabilities - Nunes, Ana Célia; Santos, Daniela Bitencourt; Leite, Márcio Fernandes Alves; Gràcia, Marta; de Souza Della Barba, Patricia Carla (Frontiers in Education, 2023)
This study aims to adapt and validate the Family Needs Assessment (FNA) scale for use with families of children and adolescents with disabilities in Brazil. Two studies were conducted. The first study involved the cross-cultural adaptation of the scale, resulting in the Brazilian version of the FNA, which is called Avaliação das Necessidades da Família (ANF). The ANF comprises 49 items with high internal consistency (α = 0.98). The second study validated the ANF using a sample of 151 families with children and adolescents with disabilities. The structure of the scale was confirmed using Structural Equation Modeling (SEM), which grouped 46 items into seven dimensions. The scale demonstrated good fit (RMSEA = 0.041, SRMR = 0.063), satisfactory convergent validity (rs = -0.27, p < 0.001), and high levels of reliability (α = 0.92, ω = 0.94) and test-retest consistency (R1F = 0.98). The ANF is a valid, reliable, and accurate measure for assessing the needs of Brazilian families with children and adolescents with disabilities under 18 years of age.We are so glad to hear from you again! We have missed working with you. I am grateful for the opportunity to edit this manuscript. I have ensured that my work meets the highest quality standards, and I look forward to receiving your feedback regarding my work on this manuscript. The manuscript has been translated and edited for grammar, language, readability, flow, clarity, and retained/conveyed your intended meaning at best. Should you have any concerns, please do not hesitate to get back to us-my best wishes for your success with the manuscript.